2011
DOI: 10.1159/000330801
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiographic Changes in Centenarians: A Study on 42 Subjects and Comparison with the Literature

Abstract: Background: Aging is associated with extensive and pervasive changes in cardiovascular structure and function, which may result in electrocardiographic alterations. The typical modifications seen in an electrocardiogram (ECG) in elders are: prolonged PR and QT intervals, QRS left-axis deviation and microvolt T wave. Several studies have included elderly people, but not long-living elderly and centenarians in particular who represent an increasing part of the population. Objective: The aim of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 15 publications
2
13
0
4
Order By: Relevance
“…3,4,[12][13][14][15][16][17][18][19] For example, the frequency of atrial fibrillation varies from 0% to 30%, and that of myocardial infarction ranges from 0% to 20% (Table VI). There are several reasons for these differences, including different enrollment criteria.…”
Section: Electrocardiogrammentioning
confidence: 99%
See 2 more Smart Citations
“…3,4,[12][13][14][15][16][17][18][19] For example, the frequency of atrial fibrillation varies from 0% to 30%, and that of myocardial infarction ranges from 0% to 20% (Table VI). There are several reasons for these differences, including different enrollment criteria.…”
Section: Electrocardiogrammentioning
confidence: 99%
“…All previous studies were single center, and most included fewer than 50 centenarians. 12,13,15,16,18 Some excluded centenarians with previous cardiac disease 12 and were performed retrospectively. 13,19 Our study was designed to avoid these biases and included a systematic approach to baseline health status, echocardiography, and follow-up.…”
Section: Electrocardiogrammentioning
confidence: 99%
See 1 more Smart Citation
“…Aging is associated with extensive changes in cardiovascular structure and function which may result in ECG abnormalities [11,12]. The clinical significance of many of these abnormalities is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…Survival prognosis of centenarians is especially important for making diagnostic and therapeutic decisions. Widespread specific cardiac anomalies have been documented by ECG in centenarians (Lakkireddy et al 2003; Rabunal-Rey et al 2012; Basile et al 2012). Survival and ECG associations have been studied by Rabunal-Rey et al (2012) who observed that atrial fibrillation is a prognostic factor for mortality and by Basile et al (2012) who did not describe any ECG findings that are predictive of survival.…”
Section: Introductionmentioning
confidence: 99%